Empowering High School Students in Nganjuk Through Scientific Writing Training: A Community Engagement Initiative - Frida Ulfa Ernawati; Lydia Rohmawati; Munasir; Zainul Arifin Imam Supardi; Evi Suaebah; Maftuhin, Wafa; Aini, Adawiyyah Nuurul Aini; Fitriana (Department of Physics, Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Surabaya (UNESA), 2025)
This community service activity was specifically aimed at high school students in Nganjuk, who generally need to improve their knowledge and skills in writing scientific articles. The objectives of this activity are to (1) provide knowledge and understanding of the methods for writing scientific works, particularly national journal articles, and (2) assist students in producing scientific papers. The training began with explanations accompanied by examples (including titles, background, methods, results, discussions, conclusions, implications, and references). Participants were then assigned writing exercises on topics of their interest to work on at home. After five days, they reconvened to present their written results. In general, the training resulted in improved knowledge and skills, as participants demonstrated increased understanding and ability in writing scientific papers compared to before the training. This improvement was reflected in the rise in average scores and the outcomes of interviews conducted after the training process. Keywords: Student, Scientific Paper, Training, Writing